2007
DOI: 10.1590/s1980-57642008dn10200010
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-operative Wisconsin card sorting test performance in patients with temporal lobe epilepsy due to hippocampal sclerosis

Abstract: Patients with temporal lobe epilepsy due to hippocampal sclerosis (TLE/HS) have a distinct neuropsychological profile, but there is still debate on whether executive dysfunction is part of this profile and also whether temporal lobe surgery can modify this dysfunction.ObjectiveTo study the presence and reversibility of executive dysfunction in patients with unilateral TLE/HS.MethodsTwenty-five patients with refractory seizures due to TLE/HS underwent presurgical evaluation which included the application of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Unlike the instructed task switches discussed so far, the flexible adaptation of behavior in naturalistic situations often requires the processing of dynamically changing feedback from the environment – an ability that is disturbed in many psychiatric (e.g., Tchanturia et al, 2012 ) and neurological (e.g., Tisser et al, 2007 ) populations. These problems in flexible behavioral adaptation are also often referred to as impairments in cognitive flexibility (e.g., Lange et al, 2016 ), and are in clinical populations commonly assessed with tasks like the Wisconsin Card Sorting Test (WCST; Heaton, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the instructed task switches discussed so far, the flexible adaptation of behavior in naturalistic situations often requires the processing of dynamically changing feedback from the environment – an ability that is disturbed in many psychiatric (e.g., Tchanturia et al, 2012 ) and neurological (e.g., Tisser et al, 2007 ) populations. These problems in flexible behavioral adaptation are also often referred to as impairments in cognitive flexibility (e.g., Lange et al, 2016 ), and are in clinical populations commonly assessed with tasks like the Wisconsin Card Sorting Test (WCST; Heaton, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4] e improved postoperative executive functioning of our SA cases in set-shifting and their stability in other aspects of executive functioning is not unprecedented. Several other previous studies have also reported enhanced [35,39,40,42] or stable [2,23] executive functioning following selective/ nonselective temporal lobe surgery. e executive dysfunction in MTLE has been attributed to the impaired function of the hippocampus and amygdala in memory retrieval and emotional processing, but also to the dynamic epileptiform abnormalities in temporofrontal networks, which may be regularized following temporal lobe surgery and lead to restored executive functioning.…”
Section: Discussionmentioning
confidence: 83%
“…e executive dysfunction in MTLE has been attributed to the impaired function of the hippocampus and amygdala in memory retrieval and emotional processing, but also to the dynamic epileptiform abnormalities in temporofrontal networks, which may be regularized following temporal lobe surgery and lead to restored executive functioning. [39] Although investigating this hypothesis requires further investigation, aberrant effective connectivity of epileptogenic zone with the executive control network has been observed in a functional imaging study on MTLE. [15] Improved executive functioning following temporal lobe surgery may also result from a decreased rate of seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies where any executive function instrument was administered in TLE was only 4 (2 WCST, 2 COWAT) of 29 compared to 21 of 27 in BD-I. One study compared RTL, LTL and HC and showed that all patients were impaired on the WCST relative to HC ( 87 ). The number of studies where any verbal memory instrument was administered was 26 of 29 in TLE compared to 14 of 27 in BD-I.…”
Section: Resultsmentioning
confidence: 99%